Whose voice do community development organizations speak? The trajectory of CBOs in Latino Pilsen in Chicago. Issue 3 (27th May 2021) - Betancur, John J.
ABSTRACT: Most of the literature and other publications on CBOs assume that they speak the voices and pursue the interests of the communities they claim to represent. While acknowledging the transformative work of some of them, recent studies have portrayed CBOs as forces of social control and poverty management. This paper reports the findings of a study examining the trajectory of CBOs in Pilsen, a Latino community in Chicago, through a historical-genealogical approach that helps identify the interests they have advocated across time and their shift from politics of resistance and advocacy to coalition politics of cooperation to their absorption into the agenda of a neoliberal administration. Guided by insights from Gramsci and Foucault, this study argues that CBOs speak different voices and advance different interests across time.